Information resources shared - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Union catalog of serials in International Agricultural Research Centers Volumes 1 and 2 published by ICRISAT Patancheru PO, AP 502 324, INDIA Also available from CTA